Corporate worship for people with dementia: rituals and sensory stimulation - Wrigley-Carr, Robyn (Journal of religion, spirituality & aging, 2021)
This article explores ways of making chapel services more accessible and meaningful for people with dementia through rituals and sensory stimulation. I was a participant-observer for 6 months at weekly chapel services at an aged care home in Sydney, Australia, and interviewed residents after those services. I also led small group sessions where residents engaged in ‘Ignatian meditation’ on a Biblical narrative. The theoretical schema for this research is von Hügel’s three 'Elements of Religion.' The best way to respond to the diminution of the 'Intellectual Element' for people with dementia is to increase the attention and nurture we give to the other two “Elements” - the 'Mystical' and the 'Institutional.' Focusing particularly upon the 'Institutional Element' through rituals and sensory stimulation can enhance experiences of God for people with dementia during corporate worship.